Algebra and Trigonometry

# A | Proofs, Identities, and Toolkit Functions

Algebra and TrigonometryA | Proofs, Identities, and Toolkit Functions

### Important Proofs and Derivations

Product Rule

$log a xy= log a x+ log a y log a xy= log a x+ log a y$

Proof:

Let $m= log a x m= log a x$ and $n= log a y. n= log a y.$

Write in exponent form.

$x= a m x= a m$ and $y= a n . y= a n .$

Multiply.

$xy= a m a n = a m+n xy= a m a n = a m+n$

$a m+n = xy log a (xy) = m+n = log a x+ log b y a m+n = xy log a (xy) = m+n = log a x+ log b y$

Change of Base Rule

$log a b= log c b log c a log a b= 1 log b a log a b= log c b log c a log a b= 1 log b a$

where $x x$ and $y y$ are positive, and $a>0,a≠1. a>0,a≠1.$

Proof:

Let $x= log a b. x= log a b.$

Write in exponent form.

$a x =b a x =b$

Take the $log c log c$ of both sides.

$log c a x = log c b x log c a = log c b x = log c b log c a log a b = log c b log c a log c a x = log c b x log c a = log c b x = log c b log c a log a b = log c b log c a$

When $c=b, c=b,$

$log a b= log b b log b a = 1 log b a log a b= log b b log b a = 1 log b a$

Heron’s Formula

$A= s( s−a )( s−b )( s−c ) A= s( s−a )( s−b )( s−c )$

where $s= a+b+c 2 s= a+b+c 2$

Proof:

Let $a, a,$ $b, b,$ and $c c$ be the sides of a triangle, and $h h$ be the height.

So $s= a+b+c 2 s= a+b+c 2$.

We can further name the parts of the base in each triangle established by the height such that $p+q=c. p+q=c.$

Using the Pythagorean Theorem, $h 2 + p 2 = a 2 h 2 + p 2 = a 2$ and $h 2 + q 2 = b 2 . h 2 + q 2 = b 2 .$

Since $q=c−p, q=c−p,$ then $q 2 = ( c−p ) 2 . q 2 = ( c−p ) 2 .$ Expanding, we find that $q 2 = c 2 −2cp+ p 2 . q 2 = c 2 −2cp+ p 2 .$

We can then add $h 2 h 2$ to each side of the equation to get $h 2 + q 2 = h 2 + c 2 −2cp+ p 2 . h 2 + q 2 = h 2 + c 2 −2cp+ p 2 .$

Substitute this result into the equation $h 2 + q 2 = b 2 h 2 + q 2 = b 2$ yields $b 2 = h 2 + c 2 −2cp+ p 2 . b 2 = h 2 + c 2 −2cp+ p 2 .$

Then replacing $h 2 + p 2 h 2 + p 2$ with $a 2 a 2$ gives $b 2 = a 2 −2cp+ c 2 . b 2 = a 2 −2cp+ c 2 .$

Solve for $p p$ to get

$p= a 2 + b 2 − c 2 2c p= a 2 + b 2 − c 2 2c$

Since $h 2 = a 2 − p 2 , h 2 = a 2 − p 2 ,$ we get an expression in terms of $a, a,$ $b, b,$ and $c. c.$

$h 2 = a 2 − p 2 = (a+p)(a−p) = [ a+ ( a 2 + c 2 − b 2 ) 2c ][ a− ( a 2 + c 2 − b 2 ) 2c ] = ( 2ac+ a 2 + c 2 − b 2 )( 2ac− a 2 − c 2 + b 2 ) 4 c 2 = ( (a+c) 2 − b 2 )( b 2 − (a−c) 2 ) 4 c 2 = (a+b+c)(a+c−b)(b+a−c)(b−a+c) 4 c 2 = (a+b+c)(−a+b+c)(a−b+c)(a+b−c) 4 c 2 = 2s⋅(2s−a)⋅(2s−b)(2s−c) 4 c 2 h 2 = a 2 − p 2 = (a+p)(a−p) = [ a+ ( a 2 + c 2 − b 2 ) 2c ][ a− ( a 2 + c 2 − b 2 ) 2c ] = ( 2ac+ a 2 + c 2 − b 2 )( 2ac− a 2 − c 2 + b 2 ) 4 c 2 = ( (a+c) 2 − b 2 )( b 2 − (a−c) 2 ) 4 c 2 = (a+b+c)(a+c−b)(b+a−c)(b−a+c) 4 c 2 = (a+b+c)(−a+b+c)(a−b+c)(a+b−c) 4 c 2 = 2s⋅(2s−a)⋅(2s−b)(2s−c) 4 c 2$

Therefore,

$h 2 = 4s(s−a)(s−b)(s−c) c 2 h = 2 s(s−a)(s−b)(s−c) c h 2 = 4s(s−a)(s−b)(s−c) c 2 h = 2 s(s−a)(s−b)(s−c) c$

And since $A= 1 2 ch, A= 1 2 ch,$ then

$A = 1 2 c 2 s(s−a)(s−b)(s−c) c = s(s−a)(s−b)(s−c) A = 1 2 c 2 s(s−a)(s−b)(s−c) c = s(s−a)(s−b)(s−c)$

Properties of the Dot Product

$u·v=v·u u·v=v·u$

Proof:

$u·v =〈 u 1 , u 2 ,... u n 〉·〈 v 1 , v 2 ,... v n 〉 = u 1 v 1 + u 2 v 2 +...+ u n v n = v 1 u 1 + v 2 u 2 +...+ v n v n =〈 v 1 , v 2 ,... v n 〉·〈 u 1 , u 2 ,... u n 〉 =v·u u·v =〈 u 1 , u 2 ,... u n 〉·〈 v 1 , v 2 ,... v n 〉 = u 1 v 1 + u 2 v 2 +...+ u n v n = v 1 u 1 + v 2 u 2 +...+ v n v n =〈 v 1 , v 2 ,... v n 〉·〈 u 1 , u 2 ,... u n 〉 =v·u$

$u·( v+w )=u·v+u·w u·( v+w )=u·v+u·w$

Proof:

$u·(v+w) =〈 u 1 , u 2 ,... u n 〉·( 〈 v 1 , v 2 ,... v n 〉+〈 w 1 , w 2 ,... w n 〉 ) =〈 u 1 , u 2 ,... u n 〉·〈 v 1 + w 1 , v 2 + w 2 ,... v n + w n 〉 =〈 u 1 ( v 1 + w 1 ), u 2 ( v 2 + w 2 ),... u n ( v n + w n )〉 =〈 u 1 v 1 + u 1 w 1 , u 2 v 2 + u 2 w 2 ,... u n v n + u n w n 〉 =〈 u 1 v 1 , u 2 v 2 ,..., u n v n 〉+〈 u 1 w 1 , u 2 w 2 ,..., u n w n 〉 =〈 u 1 , u 2 ,... u n 〉·〈 v 1 , v 2 ,... v n 〉+〈 u 1 , u 2 ,... u n 〉·〈 w 1 , w 2 ,... w n 〉 =u·v+u·w u·(v+w) =〈 u 1 , u 2 ,... u n 〉·( 〈 v 1 , v 2 ,... v n 〉+〈 w 1 , w 2 ,... w n 〉 ) =〈 u 1 , u 2 ,... u n 〉·〈 v 1 + w 1 , v 2 + w 2 ,... v n + w n 〉 =〈 u 1 ( v 1 + w 1 ), u 2 ( v 2 + w 2 ),... u n ( v n + w n )〉 =〈 u 1 v 1 + u 1 w 1 , u 2 v 2 + u 2 w 2 ,... u n v n + u n w n 〉 =〈 u 1 v 1 , u 2 v 2 ,..., u n v n 〉+〈 u 1 w 1 , u 2 w 2 ,..., u n w n 〉 =〈 u 1 , u 2 ,... u n 〉·〈 v 1 , v 2 ,... v n 〉+〈 u 1 , u 2 ,... u n 〉·〈 w 1 , w 2 ,... w n 〉 =u·v+u·w$

$u·u= | u | 2 u·u= | u | 2$

Proof:

$u·u =〈 u 1 , u 2 ,... u n 〉·〈 u 1 , u 2 ,... u n 〉 = u 1 u 1 + u 2 u 2 +...+ u n u n = u 1 2 + u 2 2 +...+ u n 2 =|〈 u 1 , u 2 ,... u n 〉 | 2 =v·u u·u =〈 u 1 , u 2 ,... u n 〉·〈 u 1 , u 2 ,... u n 〉 = u 1 u 1 + u 2 u 2 +...+ u n u n = u 1 2 + u 2 2 +...+ u n 2 =|〈 u 1 , u 2 ,... u n 〉 | 2 =v·u$

Standard Form of the Ellipse centered at the Origin

$1= x 2 a 2 + y 2 b 2 1= x 2 a 2 + y 2 b 2$

Derivation

An ellipse consists of all the points for which the sum of distances from two foci is constant:

$( x−( −c ) ) 2 + ( y−0 ) 2 + ( x−c ) 2 + ( y−0 ) 2 =constant ( x−( −c ) ) 2 + ( y−0 ) 2 + ( x−c ) 2 + ( y−0 ) 2 =constant$

Consider a vertex.

Then, $( x−( −c ) ) 2 + ( y−0 ) 2 + ( x−c ) 2 + ( y−0 ) 2 =2a ( x−( −c ) ) 2 + ( y−0 ) 2 + ( x−c ) 2 + ( y−0 ) 2 =2a$

Consider a covertex.

Then $b 2 + c 2 = a 2 . b 2 + c 2 = a 2 .$

$(x−(−c)) 2 + (y−0) 2 + (x−c) 2 + (y−0) 2 = 2a (x+c) 2 + y 2 = 2a− (x−c) 2 + y 2 (x+c) 2 + y 2 = ( 2a− (x−c) 2 + y 2 ) 2 x 2 +2cx+ c 2 + y 2 = 4 a 2 −4a (x−c) 2 + y 2 + (x−c) 2 + y 2 x 2 +2cx+ c 2 + y 2 = 4 a 2 −4a (x−c) 2 + y 2 + x 2 −2cx+ y 2 2cx = 4 a 2 −4a (x−c) 2 + y 2 −2cx 4cx−4 a 2 = 4a (x−c) 2 + y 2 − 1 4a ( 4cx−4 a 2 ) = (x−c) 2 + y 2 a− c a x = (x−c) 2 + y 2 a 2 −2xc+ c 2 a 2 x 2 = (x−c) 2 + y 2 a 2 −2xc+ c 2 a 2 x 2 = x 2 −2xc+ c 2 + y 2 a 2 + c 2 a 2 x 2 = x 2 + c 2 + y 2 a 2 + c 2 a 2 x 2 = x 2 + c 2 + y 2 a 2 − c 2 = x 2 − c 2 a 2 x 2 + y 2 a 2 − c 2 = x 2 ( 1− c 2 a 2 )+ y 2 (x−(−c)) 2 + (y−0) 2 + (x−c) 2 + (y−0) 2 = 2a (x+c) 2 + y 2 = 2a− (x−c) 2 + y 2 (x+c) 2 + y 2 = ( 2a− (x−c) 2 + y 2 ) 2 x 2 +2cx+ c 2 + y 2 = 4 a 2 −4a (x−c) 2 + y 2 + (x−c) 2 + y 2 x 2 +2cx+ c 2 + y 2 = 4 a 2 −4a (x−c) 2 + y 2 + x 2 −2cx+ y 2 2cx = 4 a 2 −4a (x−c) 2 + y 2 −2cx 4cx−4 a 2 = 4a (x−c) 2 + y 2 − 1 4a ( 4cx−4 a 2 ) = (x−c) 2 + y 2 a− c a x = (x−c) 2 + y 2 a 2 −2xc+ c 2 a 2 x 2 = (x−c) 2 + y 2 a 2 −2xc+ c 2 a 2 x 2 = x 2 −2xc+ c 2 + y 2 a 2 + c 2 a 2 x 2 = x 2 + c 2 + y 2 a 2 + c 2 a 2 x 2 = x 2 + c 2 + y 2 a 2 − c 2 = x 2 − c 2 a 2 x 2 + y 2 a 2 − c 2 = x 2 ( 1− c 2 a 2 )+ y 2$

Let $1= a 2 a 2 . 1= a 2 a 2 .$

$a 2 − c 2 = x 2 ( a 2 − c 2 a 2 )+ y 2 1 = x 2 a 2 + y 2 a 2 − c 2 a 2 − c 2 = x 2 ( a 2 − c 2 a 2 )+ y 2 1 = x 2 a 2 + y 2 a 2 − c 2$

Because $b 2 + c 2 = a 2 , b 2 + c 2 = a 2 ,$ then $b 2 = a 2 − c 2 . b 2 = a 2 − c 2 .$

$1 = x 2 a 2 + y 2 a 2 − c 2 1 = x 2 a 2 + y 2 b 2 1 = x 2 a 2 + y 2 a 2 − c 2 1 = x 2 a 2 + y 2 b 2$

Standard Form of the Hyperbola

$1= x 2 a 2 − y 2 b 2 1= x 2 a 2 − y 2 b 2$

Derivation

A hyperbola is the set of all points in a plane such that the absolute value of the difference of the distances between two fixed points is constant.

Diagram 1: The difference of the distances from Point P to the foci is constant:

$(x−(−c)) 2 + (y−0) 2 − (x−c) 2 + (y−0) 2 =constant (x−(−c)) 2 + (y−0) 2 − (x−c) 2 + (y−0) 2 =constant$

Diagram 2: When the point is a vertex, the difference is $2a. 2a.$

$( x−( −c ) ) 2 + ( y−0 ) 2 − ( x−c ) 2 + ( y−0 ) 2 =2a ( x−( −c ) ) 2 + ( y−0 ) 2 − ( x−c ) 2 + ( y−0 ) 2 =2a$

$(x−(−c)) 2 + (y−0) 2 − (x−c) 2 + (y−0) 2 = 2a (x+c) 2 + y 2 − (x−c) 2 + y 2 = 2a (x+c) 2 + y 2 = 2a+ (x−c) 2 + y 2 (x+c) 2 + y 2 = ( 2a+ (x−c) 2 + y 2 ) x 2 +2cx+ c 2 + y 2 = 4 a 2 +4a (x−c) 2 + y 2 x 2 +2cx+ c 2 + y 2 = 4 a 2 +4a (x−c) 2 + y 2 + x 2 −2cx+ y 2 2cx = 4 a 2 +4a (x−c) 2 + y 2 −2cx 4cx−4 a 2 = 4a (x−c) 2 + y 2 cx− a 2 = a (x−c) 2 + y 2 ( cx− a 2 ) 2 = a 2 ( (x−c) 2 + y 2 ) c 2 x 2 −2 a 2 c 2 x 2 + a 4 = a 2 x 2 −2 a 2 c 2 x 2 + a 2 c 2 + a 2 y 2 c 2 x 2 + a 4 = a 2 x 2 + a 2 c 2 + a 2 y 2 a 4 − a 2 c 2 = a 2 x 2 − c 2 x 2 + a 2 y 2 a 2 ( a 2 − c 2 ) = ( a 2 − c 2 ) x 2 + a 2 y 2 a 2 ( a 2 − c 2 ) = ( c 2 − a 2 ) x 2 − a 2 y 2 (x−(−c)) 2 + (y−0) 2 − (x−c) 2 + (y−0) 2 = 2a (x+c) 2 + y 2 − (x−c) 2 + y 2 = 2a (x+c) 2 + y 2 = 2a+ (x−c) 2 + y 2 (x+c) 2 + y 2 = ( 2a+ (x−c) 2 + y 2 ) x 2 +2cx+ c 2 + y 2 = 4 a 2 +4a (x−c) 2 + y 2 x 2 +2cx+ c 2 + y 2 = 4 a 2 +4a (x−c) 2 + y 2 + x 2 −2cx+ y 2 2cx = 4 a 2 +4a (x−c) 2 + y 2 −2cx 4cx−4 a 2 = 4a (x−c) 2 + y 2 cx− a 2 = a (x−c) 2 + y 2 ( cx− a 2 ) 2 = a 2 ( (x−c) 2 + y 2 ) c 2 x 2 −2 a 2 c 2 x 2 + a 4 = a 2 x 2 −2 a 2 c 2 x 2 + a 2 c 2 + a 2 y 2 c 2 x 2 + a 4 = a 2 x 2 + a 2 c 2 + a 2 y 2 a 4 − a 2 c 2 = a 2 x 2 − c 2 x 2 + a 2 y 2 a 2 ( a 2 − c 2 ) = ( a 2 − c 2 ) x 2 + a 2 y 2 a 2 ( a 2 − c 2 ) = ( c 2 − a 2 ) x 2 − a 2 y 2$

Define $b b$ as a positive number such that $b 2 = c 2 − a 2 . b 2 = c 2 − a 2 .$

$a 2 b 2 = b 2 x 2 − a 2 y 2 a 2 b 2 a 2 b 2 = b 2 x 2 a 2 b 2 − a 2 y 2 a 2 b 2 1 = x 2 a 2 − y 2 b 2 a 2 b 2 = b 2 x 2 − a 2 y 2 a 2 b 2 a 2 b 2 = b 2 x 2 a 2 b 2 − a 2 y 2 a 2 b 2 1 = x 2 a 2 − y 2 b 2$

### Trigonometric Identities

 Pythagorean Identities $cos 2 θ+ sin 2 θ=1 1+ tan 2 θ= sec 2 θ 1+ cot 2 θ= csc 2 θ cos 2 θ+ sin 2 θ=1 1+ tan 2 θ= sec 2 θ 1+ cot 2 θ= csc 2 θ$ Even-Odd Identities $cos(−θ)=cosθ sec(−θ)=secθ sin(−θ)=−sinθ tan(−θ)=−tanθ csc(−θ)=−cscθ cot(−θ)=−cotθ cos(−θ)=cosθ sec(−θ)=secθ sin(−θ)=−sinθ tan(−θ)=−tanθ csc(−θ)=−cscθ cot(−θ)=−cotθ$ Cofunction Identities $cosθ=sin( π 2 −θ ) sinθ=cos( π 2 −θ ) tanθ=cot( π 2 −θ ) cotθ=tan( π 2 −θ ) secθ=csc( π 2 −θ ) cscθ=sec( π 2 −θ ) cosθ=sin( π 2 −θ ) sinθ=cos( π 2 −θ ) tanθ=cot( π 2 −θ ) cotθ=tan( π 2 −θ ) secθ=csc( π 2 −θ ) cscθ=sec( π 2 −θ )$ Fundamental Identities $tanθ= sinθ cosθ secθ= 1 cosθ cscθ= 1 sinθ cotθ= 1 tanθ = cosθ sinθ tanθ= sinθ cosθ secθ= 1 cosθ cscθ= 1 sinθ cotθ= 1 tanθ = cosθ sinθ$ Sum and Difference Identities $cos(α+β)=cosαcosβ−sinαsinβ cos(α−β)=cosαcosβ+sinαsinβ sin(α+β)=sinαcosβ+cosαsinβ sin(α−β)=sinαcosβ−cosαsinβ tan(α+β)= tanα+tanβ 1−tanαtanβ tan(α−β)= tanα−tanβ 1+tanαtanβ cos(α+β)=cosαcosβ−sinαsinβ cos(α−β)=cosαcosβ+sinαsinβ sin(α+β)=sinαcosβ+cosαsinβ sin(α−β)=sinαcosβ−cosαsinβ tan(α+β)= tanα+tanβ 1−tanαtanβ tan(α−β)= tanα−tanβ 1+tanαtanβ$ Double-Angle Formulas $sin(2θ)=2sinθcosθ cos(2θ)= cos 2 θ− sin 2 θ cos(2θ)=1−2 sin 2 θ cos(2θ)=2 cos 2 θ−1 tan(2θ)= 2tanθ 1− tan 2 θ sin(2θ)=2sinθcosθ cos(2θ)= cos 2 θ− sin 2 θ cos(2θ)=1−2 sin 2 θ cos(2θ)=2 cos 2 θ−1 tan(2θ)= 2tanθ 1− tan 2 θ$ Half-Angle Formulas $sin α 2 =± 1−cosα 2 cos α 2 =± 1+cosα 2 tan α 2 =± 1−cosα 1+cosα tan α 2 = sinα 1+cosα tan α 2 = 1−cosα sinα sin α 2 =± 1−cosα 2 cos α 2 =± 1+cosα 2 tan α 2 =± 1−cosα 1+cosα tan α 2 = sinα 1+cosα tan α 2 = 1−cosα sinα$ Reduction Formulas $sin 2 θ= 1−cos( 2θ ) 2 cos 2 θ= 1+cos( 2θ ) 2 tan 2 θ= 1−cos( 2θ ) 1+cos( 2θ ) sin 2 θ= 1−cos( 2θ ) 2 cos 2 θ= 1+cos( 2θ ) 2 tan 2 θ= 1−cos( 2θ ) 1+cos( 2θ )$ Product-to-Sum Formulas $cosαcosβ= 1 2 [ cos(α−β)+cos(α+β) ] sinαcosβ= 1 2 [ sin(α+β)+sin(α−β) ] sinαsinβ= 1 2 [ cos(α−β)−cos(α+β) ] cosαsinβ= 1 2 [ sin(α+β)−sin(α−β) ] cosαcosβ= 1 2 [ cos(α−β)+cos(α+β) ] sinαcosβ= 1 2 [ sin(α+β)+sin(α−β) ] sinαsinβ= 1 2 [ cos(α−β)−cos(α+β) ] cosαsinβ= 1 2 [ sin(α+β)−sin(α−β) ]$ Sum-to-Product Formulas $sinα+sinβ=2sin( α+β 2 )cos( α−β 2 ) sinα−sinβ=2sin( α−β 2 )cos( α+β 2 ) cosα−cosβ=−2sin( α+β 2 )sin( α−β 2 ) cosα+cosβ=2cos( α+β 2 )cos( α−β 2 ) sinα+sinβ=2sin( α+β 2 )cos( α−β 2 ) sinα−sinβ=2sin( α−β 2 )cos( α+β 2 ) cosα−cosβ=−2sin( α+β 2 )sin( α−β 2 ) cosα+cosβ=2cos( α+β 2 )cos( α−β 2 )$ Law of Sines $sinα a = sinβ b = sinγ c a sinα = b sinβ = c sinγ sinα a = sinβ b = sinγ c a sinα = b sinβ = c sinγ$ Law of Cosines $a 2 = b 2 + c 2 −2bccosα b 2 = a 2 + c 2 −2accosβ c 2 = a 2 + b 2 −2abcosγ a 2 = b 2 + c 2 −2bccosα b 2 = a 2 + c 2 −2accosβ c 2 = a 2 + b 2 −2abcosγ$
Table A1

Figure A1
Figure A2
Figure A3

### Trigonometric Functions

Unit Circle

Figure A4
Angle $0 0$
Cosine 1 $3 2 3 2$ $2 2 2 2$ $1 2 1 2$ 0
Sine 0 $1 2 1 2$ $2 2 2 2$ $3 2 3 2$ 1
Tangent 0 $3 3 3 3$ 1 $3 3$ Undefined
Secant 1 $2 3 3 2 3 3$ $2 2$ 2 Undefined
Cosecant Undefined 2 $2 2$ $2 3 3 2 3 3$ 1
Cotangent Undefined $3 3$ 1 $3 3 3 3$ 0
Table A2
Order a print copy

As an Amazon Associate we earn from qualifying purchases.

This book may not be used in the training of large language models or otherwise be ingested into large language models or generative AI offerings without OpenStax's permission.

Want to cite, share, or modify this book? This book uses the Creative Commons Attribution License and you must attribute OpenStax.

• If you are redistributing all or part of this book in a print format, then you must include on every physical page the following attribution:
• If you are redistributing all or part of this book in a digital format, then you must include on every digital page view the following attribution: